Conformação por spray da liga amorfizável a base de ferro [(Fe0,6Co0,4)0,75B0,2Si0,05]96Nb4 - Cava, Régis Daniel (2015)
The use of amorphous metals becomes a large market in the industry of micro-components and/or milimetric machine parts, presenting excellent magnetic and mechanical properties and high glass forming ability such as the recent developed iron based alloys in the [(FexCo1-x)0.75B0.2Si0.05]96Nb4 compositions, where x = 0.1-0.5 at.%. Wherever, these properties are reached when this material is processed by techniques that impose and maintain higher cooling rates (103-106 K/s), limiting factors in order to obtain amorphous parts with centimeters in dimension. In this study, the Fe43.2Co28.8B19.2Si4.8Nb4 alloy was processed by spray forming as an alternative route to obtain amorphous deposits with large sizes. The study conducted depositions onto rotating copper rollers generating a co-lamination condition, producing larger ribbons. In a second step, depositions in industrial scale were performed using preheated cylindrical and flat substrates moving longitudinally at various speeds, producing deposits with different thickness. In a third deposition, subsequent layers were deposited due the came and back longitudinal movement of the cylindrical substrate. The microstructure of all materials were evaluated by optical and scanning electron microscopy, differential scanning calorimetry, and X-ray diffraction. The powders of all experiments and the spray-co-laminated ribbons presented fully amorphous microstructure. The first and second deposits exhibited a 1 to 2.5 mm thickness amorphous layer formed in direct contact with the substrate. The median/central regions (10 to 15 mm thickness) presented a mix of crystalline and amorphous phases or fully crystalline microstructure depending the thickness of the deposit. The third deposit was formed by ~10 layers with ~2 mm thickness each presenting fully amorphous or a mix of crystalline and amorphous phases. These results suggesting that this process is a promising potential for the production of amorphous alloys in large volumes and sizes, expanding the use of these materials.